Are They Listening? Social Media on Campuses of Higher Education - Amy F. Ratliff (JANZSSA)
Communication with students on campuses of higher education continues to drastically change. The social media phenomenon sweeping across the world creates a picturesque environment for the technologically savvy student, but often an intimidating outlook for administrators and faculty. While some higher education professionals embrace this opportunity to engage students through a new outlet, others struggle to adapt to new demands of the constantly connected, digital college student. Understanding social media and preferences of today’s college student are inherent to identifying the best practices to encourage student engagement and foster student development on college campuses.